Assessing Students’ Higher Order Thinking Skills in Geometry: A Rasch Analysis - Ningsih, Yunika Lestaria; Destiniar; Fitriasari, Putri; Octaria, Dina; Kesumawati, Nila (Department of Mathematics Education Program IPI Garut, 2023)
Kemampuan Berpikir Tingkat Tinggi merupakan tantangan penting bagi siswa di abad ke-21. Dalam sepuluh tahun terakhir, banyak penelitian nasional dan internasional telah dilakukan untuk mengidentifikasi kesulitan dan meningkatkan HOTS siswa, khususnya dalam Geometri. Tujuan dari studi ini adalah untuk mempelajari lebih lanjut tentang HOTS Geometri di kalangan siswa SMA Palembang menggunakan analisis Rasch. Data untuk studi ini dikumpulkan melalui tes tertulis 18 pertanyaan Geometri HOTS yang diujikan pada 75 siswa kelas X salah satu SMA di Pelembang. Model Rasch digunakan untuk menganalisis data hasil tes secara deskriptif. Hasil analisis data menunjukkan bahwa kemampuan HOTS siswa dalam Geometri masih kurang. Skor logit rata-rata HOTS siswa adalah -0,18. Selain itu, beberapa respons siswa tidak sesuai dengan pola model Rasch. Akibatnya, penelitian lebih lanjut diperlukan untuk meningkatkan HOTS siswa dalam Geometri. Higher Order Thinking Skills (HOTS) is an important challenge for students in the twenty-first century. In the last ten years, many national and international studies have been conducted to identify difficulties and improve students' HOTS, particularly in Geometry. The purpose of this study is to learn more about HOTS students' Geometry among Palembang senior high school students using Rasch analysis. The data for this study were gathered using a description test of 18 HOTS Geometry questions which was tested on 73 class X students at one of the high schools in Pelembang. The Rasch model was used to analyze the test result data descriptively. Data analysis results show that students' HOTS ability in Geometry is still lacking. Students' HOTS average logit score is -0.18. Furthermore, some students' responses did not match the pattern of the Rasch model. As a result, future research is required to improve students' HOTS in Geometry.